Adolescents’ Knowledge of Breastfeeding and Their Intention to Breastfeed in the Future - Čatipović, Marija (Children (Basel), 2017)
The aim of this paper is to analyze third-year secondary school students’ knowledge of breastfeeding and intention to breastfeed their children, based on the results of a questionnaire. The respondents were 154 students (101 female/43 male) of two secondary schools in Bjelovar. The students completed a questionnaire which consisted of 23 questions regarding knowledge and intention to breastfeed. The answers were analyzed statistically and different results were compared by nonparametric tests. About half of the respondents think that both partners should decide on breastfeeding and recognize the role that fathers have in initiating and maintaining breastfeeding. Only 13.64% of the respondents know that breastfeeding is to be done only on demand. Exclusive breastfeeding for 6 months, as recommended by the medical profession, is recognized by 70.13% of the students. The question on how justified is the initiation of formula together with the mother’s milk was answered correctly by 29.22% of the students. Secondary school students’ knowledge of breastfeeding is insufficient, and schools, families, social communities and other sources of information should share the responsibility for improving this. We consider it necessary to pay more attention to improving students’ knowledge of breastfeeding through school curricula.